Explorando conteúdos de Matemática básica através de problemas intrigantes - Santana, Evaldo Maurício Oliveira de (2024)
This work aims to propose some alternatives for teaching basic mathematics concepts through the investigation of intriguing problems, using the entire mathematical framework behind these problems. As examples, we selected problems that allow the exploration of topics such as areas of plane figures, the Pythagorean Theorem, linear equations, matrices, and determinants, among others. A brief experiment was conducted using concrete materials related to the Missing Square Problem, where students interacted, exchanged ideas, and identified possible techniques for solving it. An analysis of the students’ perceptions was carried out, and based on the discussion of the obtained results, we propose a didactic sequence to provide students with an enjoyable and meaningful learning experience